DASAR – DASAR FONETIK DALAM PEMBELAJARAN BAHASA - Lulu Najwah Zaid; Mulya Putra (Yayasan Haiah Nusratul Islam, 2024)
Phonetics has a very important role in language learning because it provides an in-depth understanding of the sounds of language used in everyday communication. This journal examines the basics of phonetics which include the definition of phonetics, phonemes, allophones, and the process of sound articulation that occurs during the production of language sounds. In addition, this journal discusses the application of phonetic theory in language teaching, both for mother tongue and foreign language learning. Phonetics aids the teaching of speaking and listening skills, and facilitates more accurate pronunciation through understanding the structure of sounds. The use of phonetic transcription with IPA (International Phonetic Alphabet) symbols is also explained as a tool to systematically write down and analyze language sounds. Effective phonetic learning methods, which include both practical and technological approaches, are discussed to improve students' understanding and pronunciation skills. However, there are challenges in teaching phonetics, such as difficulties in distinguishing similar sounds or in dealing with accent and dialect variations. This study emphasizes the importance of phonetics as an integral part of language teaching that not only helps students understand the language orally, but also increases their confidence in communicating effectively.